T & D Hijab / Ainor Syarfirah Osman... [et al.] - Osman, Ainor Syarfirah; Mauris, Elveona; Ford, Evianne Felliona; Juana, Farrah Dina; Abd Rashideh, Raziahtul Nadia Aznira (2015)
T&D Hijab Enterprise is a partnership with its headquarters located tn Batu 6 1/2, Jln Putatan, 88873 Kota Kinabalu, Sabah and its shop in Lot 10, 1st Floor, Centre Point, Sabah. This shop sells varieties of designs and colors of hijabs inspired from tie and dye t-shirts. T & D Hijab tries to apply this concept on scarfs and shawls intending to make women wearing hijab look more colorful and trendv. T & D Hijab is different from other hijab retailers as we give more attention to bright colors and attract customers with these various colors and designs. We also intend to excel in giving customer service to our beloved customers. Through unheralded customer attention and its unique design, T&D Hijab will slowly gain market share in the business market. Women wearing hijabs across Malaysia are always searching for new designs and colors of hijab. T&D Hijab foreseen this opportunity to provide hijabs with the finest quality from the finest material as well as designs that fit with their unique taste. This proves that T&D Hijab will have the chance to be one of the most successful hijab retailers in Malaysia. We, T&D Hijab Enterprise saw’ the opportunity that this business has the potential of success provided that it is handled efficiently. Women wearing hijabs are always looking for hijabs with new designs and at least will buy a new scarf or shawl once a month. T&D Hijab sees this as a way to prosper in this market, by taking advantage of their need